Pedagogical agent in open distance learning for the topic 'Logic and Proof' - Susaie, Clara (2023)
This study aims to design and develop an online learning platform integrated with a pedagogical agent to teach mathematics and examine the effect of the pedagogical agent in online learning on students’ performance in mathematics. The quasi-experimental research was adopted for this study with the nonequivalent control. The quantitative and qualitative mixed method is used to collect the data. A total of 89 undergraduate students who are pursuing their degree programme in Information Science and Technology at University X in Malaysia participated in this research. 32 of them belongs to the control group while the remaining 57 were in the experimental group. The study was carried out during the period of the pandemic when virtual classes were still being utilized. Hence both the control and experimental groups were attending online classes. Additionally, the experimental group was assigned to learn Mathematics with a pedagogical agent. There was a total of three phases involved in this research. The first phase is conducting the pre-test for both groups after collecting consent and general information about the participants. The second phase is an intervention where the experimental group was provided to leverage the developed system to learn about Mathematics. The final stage is the post-test, to collect the data on the performance level of the control and experimental groups. The pedagogical agent in this study has been defined as the tutor who focuses on teaching and tutoring the students to improve their performance.